2015
DOI: 10.1186/s13229-015-0052-x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant functioning of the theory-of-mind network in children and adolescents with autism

Abstract: BackgroundTheory-of-mind (ToM), the ability to infer people’s thoughts and feelings, is a pivotal skill in effective social interactions. Individuals with autism spectrum disorders (ASD) have been found to have altered ToM skills, which significantly impacts the quality of their social interactions. Neuroimaging studies have reported altered activation of the ToM cortical network, especially in adults with autism, yet little is known about the brain responses underlying ToM in younger individuals with ASD. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
117
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(124 citation statements)
references
References 79 publications
(102 reference statements)
7
117
0
Order By: Relevance
“…All these findings illustrate that activations in brain areas implicated in the ventral attention and salience‐executive RSNs are known to be weaker in the ASD population. Also, areas in the salient network and the MNS, that is, the causal flow “bridge” area (Figure ), are critical during self‐ and other‐related social and affective processes, and also known to be underactivated in ASD (Barttfeld et al., ; Kana et al., ). In line with the previously mentioned studies conducted with the help of socioemotional cognitive task‐based fMRI, we observed the same weaknesses in whole‐brain resting‐state functional connectivity, but only when analyzing temporal dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…All these findings illustrate that activations in brain areas implicated in the ventral attention and salience‐executive RSNs are known to be weaker in the ASD population. Also, areas in the salient network and the MNS, that is, the causal flow “bridge” area (Figure ), are critical during self‐ and other‐related social and affective processes, and also known to be underactivated in ASD (Barttfeld et al., ; Kana et al., ). In line with the previously mentioned studies conducted with the help of socioemotional cognitive task‐based fMRI, we observed the same weaknesses in whole‐brain resting‐state functional connectivity, but only when analyzing temporal dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence that group differences may be age-dependent comes from a study using a similar task that found no significant differences when children and adolescents with ASD were pooled together (48). Lastly, studies using theory of mind tasks report reduced activation of dorsal mPFC, TPJ, and PCC in children (49) while other studies report increased activation in adolescents with ASD (50) relative to age- matched controls. More studies are needed to clarify the developmental profile of functional deficits in ASD.…”
Section: Task-based Fmri Studies Of Atypical Dmn Functionmentioning
confidence: 91%
“…All these results suggest that the worsening of social interaction deficits associated with clinical ADHD in children with ASD might be related to the speech processing network in the left SFG. Furthermore, all the evidence supports the importance of the frontal lobe in social processing and social networks [Casartelli & Molteni, ; Clements et al, ; Greimel et al, ; Kana et al, ], which are affected by ADHD comorbidities in children with ASD. However, more research is required to enable the modeling of these systems.…”
Section: Discussionmentioning
confidence: 81%